Synthesis and Application of One-Dimensional La(OH)3 Nanostructures: An Overview - Xiang Xiao; Yu Huang; Fan Dong (Journal of Chemistry)
One-dimensional (1D) semiconductor nanomaterials are of particular importance owing to their unique properties and potential applications. This review attempts to provide a comprehensive introduction of 1D La(OH)3 nanostructures including nanowires, nanoneedles, nanobelts, and nanorods. Firstly, various strategies developed to fabricate the 1D La(OH)3 nanostructures are discussed, such as precipitation and composite-hydroxide-mediated, hydrothermal, and solvothermal methods, accompanying the description of the corresponding growth mechanisms. Then, the unique properties such as novel physical properties of 1D La(OH)3 nanostructures resulting from their unique electronic structures and numerous transition modes involving the 4f shells of these ions are represented in detail. Also, the wide applications in photocatalyst, capacitors, and photoluminescence based on the unique properties are discussed. Finally, the paper ends with a summary and some perspectives on the challenges and new directions in this emerging area.